2016
DOI: 10.1371/journal.pone.0163588
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Retractions from Korean Medical Journals in the KoreaMed Database: A Bibliometric Analysis

Abstract: BackgroundFlawed or misleading articles may be retracted because of either honest scientific errors or scientific misconduct. This study explored the characteristics of retractions in medical journals published in Korea through the KoreaMed database.MethodsWe retrieved retraction articles indexed in the KoreaMed database from January 1990 to January 2016. Three authors each reviewed the details of the retractions including the reason for retraction, adherence to retraction guidelines, and appropriateness of re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 11 publications
1
18
0
Order By: Relevance
“…Estimates in the broader literature vary by discipline and country and are often hampered by incomplete information, but typically suggest that these reasons for retractions account for well over 50% of the total, whereas retractions due to issues with data, methods or results rarely comprise more than 25% of the total (e.g. [17][18][19][20][21][22] .…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Estimates in the broader literature vary by discipline and country and are often hampered by incomplete information, but typically suggest that these reasons for retractions account for well over 50% of the total, whereas retractions due to issues with data, methods or results rarely comprise more than 25% of the total (e.g. [17][18][19][20][21][22] .…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Interestingly, duplicate publication was the most common reason (57.0%) for retraction in 111 papers that were published and retracted in KoreaMed from 1990 to January 2016 [6]. This result is markedly different from Western studies, which reported that around 15.8% to 17% of retractions were due to duplicate publication [7,8].…”
Section: Duplicate Publicationsmentioning
confidence: 86%
“…The second possibility is that the authors knew that the articles had been retracted but cited them for other reasons. In the Korean medical literature, the most common reason for retraction is duplicate publication [3]; therefore, an author may cite a retracted article without any doubt about the scientific validity of the article, which results in a positive citation. How can we efficiently reduce post-retraction citations?…”
Section: Discussionmentioning
confidence: 99%
“…Out of 217,839 articles in KoreaMed published from 1990 to January 2016, the publication type of 111 articles was retraction (0.051%). The reasons for retractions included duplicate publication (57.0%), plagiarism (8.8%), scientific error (4.4%), author dispute (3.5%), and other (5.3%); the reasons were unstated or unclear in 20.2% of cases [3]. In KoreaMed retractions due to honest error accounted for a small proportion (4.4%) of cases [4].…”
Section: Introductionmentioning
confidence: 99%